Working Conditions of Academics of a Mexican University - Hirsch-Adler , Ana (2024)
Introduction: Academics participate in various evaluation processes of their work and receive multiple demands from the universities and from society. This fact impacts the working conditions of posgraduate teachers and researchers. In the context of the Applied Ethics and Education Project, a question was included: What are the main working conditions needed to have an adequate environment for research? Purpose: Analyze the answers obtained and compare them with the results of a previous research to identify changes that have occurred in recent years. Method: It is a descriptive and interpretative study that used Qualitative Content Analysis, and in which 291 postgraduate educators from a public Mexican university participated. Results: They refer to the infrastructure and resources, having adequate and fair working circumstances for the professional group, and the need for a favorable environment of freedom and respect for the members of the community. Discussion: The results obtained and their comparison with previous research and other studies show that the difficulties to develop an autonomous professional practice are increasingly evident, especially for the new generations of university professors.